Pengembangan Media Scrapbook terhadap Keterampilan Menulis Pantun pada Kelas VII - Nurpratama, Rika Rosiana; Faznur, Lutfi Syauki (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This study is motivated by the lack of availability of learning media to write Pantun in class VII. This research and development was carried out to produce: 1) Scrapbook media in learning to write rhymes for class VII, 2) the level of feasibility and response to the developed media. The research method adopts the steps of Research and Development (R & D) Borg & Gall in Emzir which limits research in a small scale in seven stages, namely: (1) research and information gathering, (2) product design, (3) product validation, (4) product revision, (5) product trial, (6) product revision, and (7) product results. Scrapbook media is validated by two experts, namely material experts and media experts. The results of product validation were obtained: 1) The percentage of material expert validation obtained a score of 95% with very decent criteria, 2) The percentage of media expert validation obtained a score of 96.66% with very decent criteria. The overall results in general, both the validation of material experts and media experts on Scrapbook media, are very feasible to be used without improvement. In addition, the results of student responses in the initial trial obtained a score of 93.12% with very feasible criteria and the results of student responses in the limited trial obtained a score of 90.33% with very feasible criteria. Based on the data obtained, it shows that the development of Scrapbook media on rhyme writing skills in class VII gets a very good response and is suitable for use as a medium for learning to write rhymes in class VII.